Submergence times and abundance estimation of blue whales off Sri Lanka - De Vos, Asha; Christiansen, Fredrik; Pattiaratchi, Charitha; Harcourt, Robert (2011)
Very little is known about the blue whale populations in the waters of Sri Lanka. A first attempt at estimating their relative abundances using DISTANCE sampling methods is currently underway in the waters off the southern coast of the island. Surfacing behavior was quantified from focal follows of individual blue whales between January and March 2011. Estimates of submergence times will be used for generating more precise abundance estimates. Individuals were followed from a 32-foot vessel to observe surfacing patterns and breathing behaviour in the presence and absence of whalewatching boats. Time at first surface, length of surface interval, number of blows and final dive time were collected. The data gathered was analysed using a hidden Markov model (HMM) to identify whether dive duration was uniform or whether dives could be classified using surface interval and submergence time. The preliminary results show that the whales performed two types of dives; ‘regular’ and ‘deep’ dives with Inter Breath Intervals (IBI) of 22.0s (SD=4.7) and 635.6s (SD=405.4) respectively. Blue Whales off southern Sri Lanka spend 75% of their time performing ‘regular’ dives. Accordingly; we estimated that their mean IBI was approximately 173s. These preliminary results obtained using HMM may provide a more accurate correction factor than that obtained from the raw data. This may refine estimates of whale density and abundance for the area.